Optimization of onion peels in the control of hydroponic brassica rapa L pests - Fatimah, Fatimah; Lestariningsih, Nanik; Swestyani, Sondra (JPBIO (Jurnal Pendidikan Biologi), 2024)
Pest attacks on plants are the most common problem faced by farmers. One type of pest that most often attacks plants with hydroponic methods is the Aphis gossypii pest.  Seeing this, an innovation must be developed in controlling pests that are more environmentally friendly. This study aimed to determine how influential the use of shallot and garlic skin baths as pest control in hydroponic Brassica rapa L. plants with concentrations of 25%, 50%, and 75%. This research is an experimental study in which the data obtained is processed using the ANOVA method. The results of the study based on the data processing results showed that there was less visible difference between the three treatments given for four weeks of treatment. So, it can be in the application of natural pesticides, which can be given in the first week with a concentration of 25%, in the second week 50%, and in the third week and fourth week 75%.